How do Money, Sex, and Stress Influence Marital Instability? - E. Jeffrey Hill; David B. Allsop; Ashley B. LeBaron; Roy A. Bean (Journal of Financial Therapy, 2017)
This study explored how money and sex simultaneously predicted marital instability, and what financial therapists might focus on with clients to address problems in these areas. Specifically, this paper concurrently examined the relationship of marital instability to financial and family stressors (financial stressors, work-family conflict, and parenting stressors); financial and sexual resources (couple income and couple sexual frequency); and financial and sexual perceptions (financial dissatisfaction and sexual dissatisfaction). Couple financial communication and couple relational communication were explored as intervention points for financial therapists. Data came from Wave 2 of the Flourishing Families data set (N = 301). Data were organized using the ABC-X model of family stress (Hill, 1949) and integrated with Gottman's research on the importance of relational communication (Navarra, Gottman, & Gottman, 2016). Path analysis revealed that family financial stressors were associated with greater financial dissatisfaction and sexual dissatisfaction. Work-family conflict was associated with greater couple income, and parenting stressors were positively associated with sexual dissatisfaction. Couple income was associated with lower financial dissatisfaction, and sexual frequency was associated with lower sexual dissatisfaction. Both financial dissatisfaction and sexual dissatisfaction predicted greater marital instability; however, healthy couple financial communication and healthy couple relationship communication fully mediated these two associations. This suggests that if financial therapists help clients to communicate more productively about money and sex, problems such as financial stress, work-family conflict, inadequate income, and conflicts about sexual frequency may be less likely to lead to divorce.
Keywords: money; sex; stress; communication; marital stability; family finance; family stress theory; ABC-X Model; financial therapy; marriage and family therapy